SLEEP QUALITY IN CARDIAC PATIENTS: A BIBLIOMETRIC ANALYSIS - Al Farisi, Muhammad Farhan; Rosa, Elsye Maria (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
ABSTRACT Background: Heart disease has become one of the leading causes of death in various countries worldwide. Poor sleep quality has been associated with an increased risk of developing heart disease, as well as worsening the prognosis of patients already diagnosed with heart disease. In an effort to understand the relationship between sleep quality and cardiovascular conditions, bibliometric research becomes crucial in identifying current trends, patterns, and research focuses.Objective: This research aims to provide information through bibliometric analysis of publication trends, literature development, and publication information analysis regarding research on sleep quality in patients with heart disease.Method: The systematic literature search was used as a method, with bibliographic sources searched in journal databases, including PubMed, ProQuest, and Scopus, from 2018 to 2022. The selection criteria chosen for this review were journals focusing on patients with heart disease, patients with changes in health status, sleep quality, publications within the last 5 years, and research designs such as cross-sectional studies, cohorts, descriptive studies, quasi-experiments, and prospective studies.Result : Based on the study, 12 journals were found for review. There are numerous correlations in the poor quality of sleep among cardiac patients, such as alcohol consumption, smoking, sleep latency, male gender, female, diabetes, hypertension, and heart disease. Conclusion : The conclusion of this review is that there are factors that can be maintained to support positive changes in having sleep quality.  Keywords: Quality of sleep, Cardiac Patient, Analysis Bibliometric